2016
DOI: 10.1007/s11892-016-0734-6
|View full text |Cite
|
Sign up to set email alerts
|

The Promise of Mesenchymal Stem Cell Therapy for Diabetic Kidney Disease

Abstract: Diabetes mellitus (DM) commonly leads to progressive chronic kidney disease despite current best medical practice. The pathogenesis of diabetic kidney disease (DKD) involves a complex network of primary and secondary mechanisms with both intra-renal and systemic components. Apart from inhibition of the renin angiotensin aldosterone system, targeting individual pathogenic mediators with drug therapy has not, thus far, been proven to have high clinical value. Stem or progenitor cell therapies offer an alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 148 publications
1
47
0
Order By: Relevance
“…As previously reported, cell-based strategy utilizing MSCs therapy is very promising for tissue regeneration [111], including DN [35, 58]. MSCs show preferential migration toward sites of inflammation, injury, and cancer, suggesting that these cells may be attractive hypoimmunogenic cellular vehicles for drug and gene delivery [112], as well as trophic factors to damaged diabetic kidney.…”
Section: Perspectivesmentioning
confidence: 95%
See 2 more Smart Citations
“…As previously reported, cell-based strategy utilizing MSCs therapy is very promising for tissue regeneration [111], including DN [35, 58]. MSCs show preferential migration toward sites of inflammation, injury, and cancer, suggesting that these cells may be attractive hypoimmunogenic cellular vehicles for drug and gene delivery [112], as well as trophic factors to damaged diabetic kidney.…”
Section: Perspectivesmentioning
confidence: 95%
“…MSCs secrete a wide array of cytokines and growth factors, which can suppress the immune system, fibrosis oxidative stress, and apoptosis and enhance angiogenesis [35]. …”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that MSC therapy can be useful for the treatment of complications associated with DM, including cardiovascular complications, diabetic kidney disease and diabetic retinopathy [4,[9][10][11]. However, to our knowledge, the impact of MSC therapy on thyroid H 2 O 2 generation and thyroid function in DM remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Stem or progenitor cell therapies offer an alternative strategy for modulating complex disease processes by suppressing multiple pathogenic pathways and promoting pro-regenerative mechanisms. Mesenchymal stem cells (MSCs) have shown particular promise in this regard based on their availability from adult tissues and their diverse mechanisms of action, including secretion of paracrine anti-inflammatory and cytoprotective factors [2]. …”
Section: Introductionmentioning
confidence: 99%